Comparing those who do, might and will not invest in sustainable funds: a survey among German retail fund investors - Anett Wins; Bernhard Zwergel (Business Research, 2016)
In this paper, we present the results of an online questionnaire among private German mutual fund investors. In an exploratory nature, we empirically analyze the differences between three groups: sustainable investors, conventional investors that are either generally interested or those that are not interested at all to invest in socially responsible (SR) funds. We provide evidence on motives and attitudes of these three investor groups, showing that SR fund investors are quite similar to those interested in investing sustainably and very different from those who only consider investing conventionally. All three groups agree that sustainable actions of a company affect its stock price positively. Yet, they all believe that SR funds perform worse than conventional funds. Nevertheless, some still invest in SR funds. Consequently, different motives and attitudes are the determining factors when it comes to making an investment decision. These differences will be extensively discussed on the following pages.
Keywords: G11; 650; Ethical investors; Sustainable investors; Pro-social attitudes; Socially responsible investment; SRI; Survey